Andrei Siniavskii : a hero of his time? - Markesinis, Eugenie (Studies in Russian and Slavic literatures, cultures and history., 2013)
This groundbreaking critical biography of Andrei Siniavskii (1925-1997) as a writer in and of his time shows how this subtle and complex author found his way in a society polarized into heroes and villains, patriots and traitors, how he progressed from identification with the value system and ideology of his time to reaction against it, and his dissidence expressed in literary terms. Based on a close reading of his work, Andrei Siniavskii: A Hero of his Time? explores the way in which Siniavskii's art does not simply reflect the circumstances of his life and times but is actively shaped by an intricate commerce between the two.